Warming of subarctic tundra increases emissions of all three important greenhouse gases – carbon dioxide, methane, and nitrous oxide - Voigt, Carolina; Lamprecht, Richard E.; Marushchak, Maija E.; Lind, Saara E.; Novakovskiy, Alexander; Aurela, Mika; Martikainen, Pertti J.; Biasi, Christina (Global change biology, 2017)
Rapidly rising temperatures in the Arctic might cause a greater release of greenhouse gases (GHGs) to the atmosphere. To study the effect of warming on GHG dynamics, we deployed open‐top chambers in a subarctic tundra site in Northeast European Russia. We determined carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) fluxes as well as the concentration of those gases, inorganic nitrogen (N) and dissolved organic carbon (DOC) along the soil profile. Studied tundra surfaces ranged from mineral to organic soils and from vegetated to unvegetated areas. As a result of air warming, the seasonal GHG budget of the vegetated tundra surfaces shifted from a GHG sink of −300 to −198 g CO2–eq m−2 to a source of 105 to 144 g CO2–eq m−2. At bare peat surfaces, we observed increased release of all three GHGs. While the positive warming response was dominated by CO2, we provide here the first in situ evidence of increasing N2O emissions from tundra soils with warming. Warming promoted N2O release not only from bare peat, previously identified as a strong N2O source, but also from the abundant, vegetated peat surfaces that do not emit N2O under present climate. At these surfaces, elevated temperatures had an adverse effect on plant growth, resulting in lower plant N uptake and, consequently, better N availability for soil microbes. Although the warming was limited to the soil surface and did not alter thaw depth, it increased concentrations of DOC, CO2, and CH4 in the soil down to the permafrost table. This can be attributed to downward DOC leaching, fueling microbial activity at depth. Taken together, our results emphasize the tight linkages between plant and soil processes, and different soil layers, which need to be taken into account when predicting the climate change feedback of the Arctic. Experimental air warming increased emissions of all three greenhouse gases (GHGs), including the highly understudied N2O, clearly demonstrating the need to include N2O in future Arctic GHG budgets. Increased GHG fluxes were regulated by changes in plant functioning and biogeochemical processes, leading to an enhanced soil input of labile carbon compounds via leaching. Plants were also identified as the main regulator of arctic N2O emissions. Importantly, we highlight the tight linkages between plant and soil processes, and the interactions between the top‐soil and deeper soil layers, in regulating arctic GHG exchange.